STUDI LITERATUR : ANALISIS PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS DIGITAL TERHADAP PEMENUHAN KEBUTUHAN BELAJAR PESERTA DIDIK SEKOLAH DASAR - Sari Mubarokati; Naila Aniyah; Rose Widodari; Jauhar Latipah; Ahmad Suriansyah; Wahdah Refia Rafianti (STKIP Subang, 2025)
This study aims to analyze the influence of interactive digital-based learning media on fulfilling elementary school students’ learning needs. The research employed a literature study with a descriptive qualitative approach by analyzing various relevant previous studies. The results indicate that interactive digital learning media can enhance students’ learning motivation, active participation, and learning independence. Digital media also support the fulfillment of cognitive, affective, and social learning needs through engaging visual, audio, and interactive features. Theoretically, digital media align with the principles of constructivism, connectivism, and social learning theories, emphasizing active, collaborative, and adaptive learning experiences. Therefore, the use of interactive digital-based learning media serves not only as a technological tool but also as an effective pedagogical strategy to improve the quality of learning in elementary education.